AB0324 Comparison of DAS28-CRP with 3 and 4 variables in rheumatoid arthritis patients treated with biological agents in the daily clinic. (23rd January 2014) - Madsen, O.R.
Abstract : Background: DAS28 based on CRP (DAS28-CRP) may be calculated using three or four variables. DAS28-CRP(4) is computed using four variables: swollen and tender joint count, CRP and patient global assessment. DAS28-CRP(3) only includes swollen and tender joint count and CRP as patient global assessment has been excluded. The thresholds for low and high disease activity and for improvements are the same for the two scores [1]. Objectives: The aim of the study was, for the first time, to compare the two DAS scores regarding sensitivity to change and to assess the agreement between the scores and their changes on group and subject level after initiation of biological treatment in an observational clinical setting. Methods: Baseline and 4 months disease activity data from 239 rheumatoid arthritis patients treated with a biological agent were extracted from the Danish registry for biological treatment (DANBIO). Effect sizes (ES) [mean DAS change/SD baseline] as well as disease activity and improvement levels according to the DAS thresholds were assessed for each of the two DAS versions. The Bland-Altman method was used to examine the agreement between the scores on subject level. Limits of agreement (LOA) were estimated as the mean difference between duplicate measurements (the bias) ±1.96SD, where SD is the standard deviation of all the differences. This means that 95% of the differences will lie between these limits. Results: DAS28-CRP(4) at baseline was 4.8±1.2 versus 4.6±1.1 for DAS28-CRP(3) (p<0.0001). The bias of DAS28-CRP(3) at baseline was -0.28±0.32 (p<0.0001) with LOA of -0.92 and 0.36. After 4 months of biological treatment, the scores for DAS28-CRP(4) and DAS28-CRP(3) had improved by –1.39±1.34 (p<0.0001) and –1.18±1.22 (p<0.0001), respectively.The bias for DAS28-CRP(3) at this time point was -0.07±0.31 (p<0.0001) with LOA of -0.69 and 0.55. The bias for the change in DAS28-CRP(3) was 0.21±0.35 (p<0.0001) with LOA of -0.49 and 0.91.The two DAS-scores were highly correlated at both baseline (r =0.96, p<0.0001) and at 4 months (r =0.97, p<0.0001). The changes in the DAS-scores were also highly correlated (r =0.97, p<0.0001). ES for DAS28-CRP(4) was 1.2±1.1 vs. 1.1±1.1 for DAS28-CRP(3) (p<0.0001). Compared to DAS28-CRP(4), DAS28-CRP(3) categorized 33% fewer patients as having a high level of disease activity both at baseline and at 4 months, categorized 8% fewer patients as good responders and 12% more patients as non-responders. Conclusions: DAS28-CRP (3) and DAS28-CRP(4) agree well on group level but may differ widely in individual patients. DAS28-CRP(3) yielded lower scores, categorized less patients as having high disease activity level and was less sensitive to change than DAS28-CRP(4). References: http://www.das-score.nl Disclosure of Interest: None Declared